Malignant phyllodes tumour presenting as a massive fungating breast mass and silent thrombo-embolism. (2015) - Bourke, Anita G.; McCreanor, Madeleine; Yeo, Allen; Weber, Dieter; Bartlett, Anthony; Backhouse, Anastasia
Highlights: Massive phyllodes tumour has a higher chance of being malignant. Staging imaging is undertaken to confirm and define local chest wall invasion. An associated silent DVT/pulmonary embolism should be considered. Pre-operative diagnosis of DVT/Pulmonary embolism changes peri-operative planning. Peri-operative morbidity/mortality is reduced by recognising DVT/Pulmonary embolism. Abstract: Introduction: We report an unusual case of a massive malignant phyllodes tumour that had almost replaced the entire breast presenting with severe chronic blood loss, extensive deep venous thrombosis (DVT) and a silent pulmonary embolus. Presentation: Long-standing neglected massive fungating ulcerative mass larger than the left haemothorax. Discussion: Phyllodes tumours are rare fibro-epithelial breast lesions that have the propensity to grow rapidly to a large size if neglected. Larger tumours are more likely to be malignant with an overall metastatic rate around 10%. An incidental pulmonary embolus arising from extensive silent lower limb deep vein thrombosis requiring an IVC filter complicated the surgical management. Conclusion: Phyllodes tumours are rare and account for approximately 0.3–0.5% of all breast tumours[1] . They have the propensity to be fast growing. However, tumours reaching a massive size (>10 cm) are rare with few reports in the literature.